REINFORCING THE JURISDICTION OF THE ADMINISTRATIVE COURT: THE SHIFTING BURDEN OF PROOF MODEL IN OMISSION DISPUTES ON DISASTER MANAGEMENT - Muhamad Fadillah; Moh. Fadli; Maria Fransiska Walintukan (CV. RADJA PUBLIKA, 2025)
This article aims to analyze and propose the application of the shifting burden of proof model in resolving omission disputes within the Indonesian Administrative Court (PTUN), particularly in the context of disaster management. Omission disputes frequently arise from governmental negligence in fulfilling legal obligations that are clearly stipulated by statutory regulations. The heavy burden of proof imposed on the claimant, combined with the unequal access to administrative documents, poses significant challenges in proving such negligence. This article adopts a normative-qualitative approach, using the case study of Decision No. 10/G/TF/2022/PTUN.PLG to illustrate the practical issues encountered by the public. The proposed model of shifting the burden of proof provides a pathway for the Administrative Court to reinforce its jurisdiction as a guardian of governmental accountability, while also serving as a corrective mechanism against state negligence in the administration of disaster management.